Use distributie property which is
a(b+c)=ab+ac
therefor
6x(x-4)=6x^2-24x
distribute the negative 1 infroont of the (9x-1)
-1(9x-1)=-9x+1
now we have
6x^2-24x-16x^2-9x+1
gropu like terms
6x^2-16x^2-24x-9x+1
add like terms
-10x^2-33x+1 is simplest form
The final amount of the compound interest after 6 years would be $ 294, 122, 500
<h3>How to determine the final amount</h3>
The formula for the final amount is given as;
![A = P( 1 + \frac{r}{n}) ^n^t](https://tex.z-dn.net/?f=A%20%3D%20P%28%201%20%2B%20%5Cfrac%7Br%7D%7Bn%7D%29%20%5En%5Et)
Where
A = final amount
P = principal interest
r = interest rate
n = number of times
t = time of periods
We have,
A =
![( 1 + \frac{6}{1}) ^1^*^6](https://tex.z-dn.net/?f=%28%201%20%2B%20%5Cfrac%7B6%7D%7B1%7D%29%20%5E1%5E%2A%5E6)
A = ![2500 ( 7)^6](https://tex.z-dn.net/?f=2500%20%28%207%29%5E6)
A =
× ![117, 649](https://tex.z-dn.net/?f=117%2C%20649)
A =$ ![294, 122, 500](https://tex.z-dn.net/?f=294%2C%20122%2C%20500)
Thus, the final amount of the compound interest after 6 years would be $ 294, 122, 500
Learn more about compound interest here:
brainly.com/question/24924853
#SPJ1
Answer:
x=8 or -8
Step-by-step explanation:
64 squared = 8 or -8
8x8=64
-8x-8 = 64